2003
DOI: 10.1038/sj.bjp.0704999
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of kinin B1 receptor in the lung of streptozotocin‐diabetic rat: autoradiographic and functional evidence

Abstract: 1 The function and autoradiographic binding expression of kinin B 1 receptors were evaluated in the lungs of Streptozotocin (STZ)-diabetic rats. -BK in STZ-diabetic rats was signi®cantly reduced after treatment with insulin (2 U per day, s.c. over 4 days) or with an anti-PMN antibody (0.1 ml of a 1 : 20 dilution, i.pl. 5 min earlier). 5 Speci®c B 1 receptor binding sites were seen in lung sections from both control and STZ-diabetic rats, yet the density of labelling was much greater in diabetic rats and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Thus, the administration of fucoidin, an anti-CD18, or a selective PAF receptor antagonist consistently prevented LPS from facilitating des-Arg 9 -BK-induced edema. This is consistent with our previous studies demonstrating the involvement of neutrophils in the modulation of B 1 receptors in vivo (37,65). Overall, these studies firmly establish a role for neutrophils in the sequence of events leading to the functional up-regulation of B 1 receptors after several inflammatory stimuli in vivo (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the administration of fucoidin, an anti-CD18, or a selective PAF receptor antagonist consistently prevented LPS from facilitating des-Arg 9 -BK-induced edema. This is consistent with our previous studies demonstrating the involvement of neutrophils in the modulation of B 1 receptors in vivo (37,65). Overall, these studies firmly establish a role for neutrophils in the sequence of events leading to the functional up-regulation of B 1 receptors after several inflammatory stimuli in vivo (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…These observations are of great potential significance, as a peptide B 1 receptor antagonist, presumably via an anti-inflammatory effect, prevented the progression of the insulin-dependent diabetes. Established streptozotocin-induced diabetes in rodents has been repeatedly shown to be associated with strong B 1 receptor expression in peripheral tissues with various functional consequences when exogenous des-Arg 9 -BK (Cloutier and Couture, 2000;Campos et al, 2001;Abdouh et al, 2003;Vianna et al, 2003) or an ACE inhibitor (Mage et al, 2002) are administered. Interestingly, this type of diabetes in mice is associated with a state of hyperalgesia that is reversed by peptide antagonists of the B 1 receptor (Gabra and Sirois, 2002), suggesting some activation of the endogenous kallikrein-kinin system.…”
Section: Diabetesmentioning
confidence: 99%
“…The modeled pathology is insulin-dependent diabetes without insulin treatment, a wasting disease with high blood cytokine levels and a particularly low life expectancy in humans in the preinsulin era. Insulin treatment of diabetic rats reversed the up-regulation of the B 1 receptor in streptozotocin-treated rats (radioligand binding, function, Vianna et al, 2003). The forms of diabetes that the physicians treat today are no longer wasting diseases, and many observations based on the streptozotocin models have an uncertain significance for the complications of diabetes, but remain interesting as models of systemic inflammatory responses.…”
Section: Diabetesmentioning
confidence: 99%
“…Up-regulation of the bradykinin B 1 receptor has been found in airway and other tissues during inflammation (Christiansen et al, 2002;Hara et al, 2008;Vianna et al, 2003); the hyperresponsiveness to bradykinin or up-regulation of the bradykinin B 2 receptor has been reported in airway inflammation models (Ellis et al, 2004;Kim et al, 2005). Data obtained previously have demonstrated that NF-κB signaling plays an important role in the process up-regulation of the bradykinin B 1 receptor (Moreau et al, 2007;Ni et al, 1998;Sabourin et al, 2002;Schanstra et al, 1998).…”
Section: Discussionmentioning
confidence: 94%